Leadership Attitude of office Heads toward Employees and Leadership Styles - Abun, Damianus; Catbagan, Nimfa, C.; Magallanes, Theogenia; Rodrigo, Robert; Quinto, Egdona A. (Technium Social Sciences Journal, 2021)
The objective of the study was to investigate the effect of leadership attitude toward employees and the leadership styles practiced by the office heads. To establish the theoretical foundation of the study, related literature was reviewed. The study used a descriptive correlational research design and the questionnaires were used to gather the data. Descriptive and inferential statistics were used to interpret the data. Weighted mean was used to determine the level of leadership attitude and leadership styles. Pearson r correlation was used to determine the correlation between the leadership attitude and the leadership styles of office heads. As a whole, the leadership attitude of office heads toward employees was high (4.18) and the leadership styles were moderate (3.46). Overall, the study found that there is no correlation between leadership attitude toward employees and leadership styles of office head and therefore the hypothesis of the study is rejected.